Use of somatostatin receptor PET to differentiate between high-risk and low-risk atherosclerotic lesions: a prospective clinical study. (25th February 2016) - Tarkin, Jason M; Joshi, Francis R; Evans, Nicholas R; Groves, Ashley M; Gopalan, Deepa; Manavaki, Roie; Kirkpatrick, Peter J; Coughlin, Patrick A; Buscombe, John R; Fryer, Tim D; Bennett, Martin R; Davenport, Anthony P; et al.
Abstract: Background: Inflammation drives atherosclerotic plaque rupture that underlies most myocardial infarctions and strokes. Upregulation of somatostatin receptor subtype-2 (SST2 ) occurs on the cell surface of activated macrophages, offering a potential imaging target for tracking vascular inflammation. We tested the hypothesis that SST2 PET-CT imaging with 68 Ga-DOTATATE can detect high-risk carotid and coronary plaque inflammation. We then compared its efficacy with 18 F-fludeoxyglucose ( 18 F-FDG), which has limited use in coronary imaging. Methods: Prospective sequential 68 Ga-DOTATATE PET and 18 F-FDG PET imaging, plus CT angiography, were performed in 42 patients with either a recent cardiovascular event (within 3 months of imaging) or stable atherosclerosis, and at least 30% carotid or coronary artery stenosis. Images were analysed, with investigators masked to clinical details, to derive median (IQR) maximum arterial tissue-to-background ratio (TBR). Arterial TBRs were statistically evaluated against clinical and biochemical data, as well as CT-derived plaque morphology. Findings: 70 carotid arteries and 230 coronary segments were included. 24 patients (57%) had a recent cardiovascular event. 68 Ga-DOTATATE TBR (1·98 [1·67–2·14]) was higher in symptomatic carotid arteries than in contralateral arteries (1·77 [1·46–2·08], p=0·0031) and asymptomatic plaques (1·49 [1·36–1·66], p=0·0012). 18 F-FDG TBR was also higher on the symptomatic side (1·68 [1·49–1·97] vs 1·51 [1·44–1·80], p=0·0081). The two PET tracers were moderately correlated ( r =0·40, p=0·0007). Coronary SST2 signals were visible in all patients, but high myocardial muscle 18 F-FDG uptake was prohibitive in 27 patients (64%). Culprit coronary arteries had higher 68 Ga-DOTATATE TBR (2·91 [2·69–4·08]) than the highest non-culprit segment (2·61 [1·94–3·01], p=0·0078), stable stented (2·00 [1·51–2·70], p=0·0063), and calcified (1·64 [1·33–2·04], p<0·0001) plaques. SST2 signal from culprit and high-risk coronary arteries was correlated with total cholesterol (r=0·44, p=0·042). Interpretation: We have shown that measurement of vascular inflammation with SST2 PET is feasible and differentiates high-risk and low-risk carotid and coronary lesions. High target specificity, low myocardial binding, and lower cost owing to generator-production give advantage to 68 Ga-DOTATATE over 18 F-FDG for atherosclerosis imaging. Correlations with 18 F-FDG TBR and serum cholesterol further support the vascular SST2 signal as a potential prognostic biomarker to identify patients most at risk of future cardiovascular events. Funding: Wellcome Trust.